Alternative farming systems, biotechnology, drought stress and ecological fertilisation - Lichtfouse, Eric; SpringerLink (Online service). (Dordrecht [Netherlands] New York Springer, 2011)
Sustainable agriculture is a rapidly growing field aiming at producing food and energy in a sustainable way for humans and their children. Sustainable agriculture is a discipline that addresses current issues such as climate change, increasing food and fuel prices, poor-nation starvation, rich-nation obesity, water pollution, soil erosion, fertility loss, pest control, and biodiversity depletion. Novel, environmentally-friendly solutions are proposed based on integrated knowledge from sciences as diverse as agronomy, soil science, molecular biology, chemistry, toxicology, ecology, economy, and social sciences. Indeed, sustainable agriculture decipher mechanisms of processes that occur from the molecular level to the farming system to the global level at time scales ranging from seconds to centuries. For that, scientists use the system approach that involves studying components and interactions of a whole system to address scientific, economic and social issues. In that respect, sustainable agriculture is not a classical, narrow science. Instead of solving problems using the classical painkiller approach that treats only negative impacts, sustainable agriculture treats problem sources. Because most actual society issues are now intertwined, global, and fast-developing, sustainable agriculture will bring solutions to build a safer world. This book series gathers review articles that analyze current agricultural issues and knowledge, then propose alternative solutions. It will therefore help all scientists, decision-makers, professors, farmers and politicians who wish to build a safe agriculture, energy and food system for future generations
1. Thinking by Connections and the Dynamics of Nature for Food Production; Dr. Clara Ceppa. -2. Transgenic Bt Corn Hybrids and Pest Management in the USA; Dr. Siddharth Tiwari -- 3. Marker-Assisted Breeding in Higher Plants; Dr. Mehboob Rahman -- 4. Phytoremediation Techniques for Pesticide Contaminations; Dr. Sophie Pascal-Lorber -- 5. Sustainable Land Use and Agricultural Soil; Dr. Victor Hugo Duran -- 6. Drought Stress Effect on Crop Pollination, Seed Set, Yield and Quality; Dr. Ahmad Alqudah -- 7. Ecological Fertilization; Dr. György Füleky -- 8. Tropical Homegardens in Bangladesh, Characteristics and Sustainability; Dr. Mahbubul Alam -- 9. Arbuscular Mycorrhizal Fungi and Rhizobium to Control Plant Fungal Diseases; Dr. Mohdsayeed Akhtar -- 10. Sustainable Crop production using Saline and Sodic Irrigation Waters; Dr. Om Parkash Choudhary -- 11. Climate Change Impact on Forestry in India; Dr. Geetanjali Kaushik
Title from title screen (viewed September 12, 2023)
Electronic reproduction
Keywords: Sustainable agriculture; Agricultural biotechnology; Agriculture -- Effect of drought on; Fertilizers -- Environmental aspects